Dampak Kebijakan Sistem Kerja Work From Home Pada Lembaga Pemasyarakatan Kelas II b Kayu Agung - Sulastri, Sri; Sakir, Icuk M.; Depriadi, Depriadi (@-Publik: Jurnal Administrasi Publik, 2021)
Employee performance compared to Work From Office where employees work in offices and also use the facilities provided by the company and are also adequate to support their performance. The workload that requires a team is also faster and more efficient when carried out in the office, in contrast to the current situation which requires employees to carry out all their work from home. The purpose of this study was to analyze the impact of the Work From Home System Policy on the Class IIB Kayu Agung Penitentiary. The problem in this study is that the working hours of employees become irregular, employees who are used to conventional office situations find it difficult to coordinate with co-workers and the Office of the Class IIB Kayu Agung Penitentiary has difficulty measuring worker productivity and can make employees less motivated at work. The data analysis technique used in this research is qualitative data analysis technique. This study concludes that overall the Work From Home Work System Policy at the Class IIB Kayu Agung Correctional Institution has been running as it should. Although in practice there are still obstacles in terms of irregular working hours, employees who are used to conventional office situations find it difficult to coordinate with co-workers and the Office of the Class IIB Kayu Agung Penitentiary has difficulty measuring worker productivity and can make employees less motivated at work Keywords: Impact, Policy, Work System, Work From Home